The multi-objective optimization of combustion system operations based on deep data-driven models. (1st September 2019) - Tang, Zhenhao; Zhang, Zijun
Abstract: Advancing methods for modeling combustion systems and optimizing their operations is beneficial to improve the combustion performance. This paper develops a deep data-driven framework for the optimization of combustion system operations. First, a deep belief network based method is developed to model both of the combustion efficiency and the NOx emission. Next, a multi-objective optimization model is developed by integrating the deep belief network based models, the considered operational constraints, and the control variable constraints. Two objectives, maximizing the combustion efficiency and minimizing the NOx emission, are considered in the optimization. Due to the nonlinearity and complexity of the optimization model, traditional exact solution methods are not applicable to solve it. A recently presented swarm intelligence method, the JAYA algorithm, is applied to obtain the optimal solutions of the developed optimization model. Advantages of using JAYA are proved by benchmarking against well-known computational intelligence methods. The feasibility and effectiveness of the developed framework for optimizing the combustion process using industrial data is validated by computational experiments. Results demonstrate the potential of further improving both of the combustion efficiency and NOx emission by optimizing control settings of the combustion system. Highlights: The multi-objective optimization of combustion system operations using deep data-driven models is studied. A deep belief network based method is developed to model the combustion efficiency and NOx emission. A data-driven multi-objective optimization model of combustion process operations is developed. A JAYA algorithm is firstly applied to solve the developed optimization model. Computational results show the potential of further improving the combustion performance based on the developed model.